1987
DOI: 10.1038/ki.1987.202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dialysate composition on intercompartmental fluid shift

Abstract: Effect of dialysate composition on intercompartmental fluid shift and hemodynamics was studied in 12 patients during 1.5 or 2 hours of hemodialysis without net ultrafiltration, using high (H;Na 154 mmol/liter), normal (N;Na 140 mmol/liter) or low (L:Na 126 mmol/liter) concentration dialysate. H dialysate was associated with a small (0.9%) increase in blood volume, a larger increase in plasma volume and a decrease in erythrocyte volume. L dialysate resulted in a 2.3% decrease in blood volume, a larger decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…As we find an increase in blood volume, the decrease in osmolarity by decreased plasma urea concentrations does not result in a volume shift towards the intracellular compartment. These findings are in accordance with those of Fleming et al [14], who previously observed that changes in blood volume are not correlated with urea efflux. However, in this study there was a positive correlation between changes in blood volume and the extracellular sodium concentration.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As we find an increase in blood volume, the decrease in osmolarity by decreased plasma urea concentrations does not result in a volume shift towards the intracellular compartment. These findings are in accordance with those of Fleming et al [14], who previously observed that changes in blood volume are not correlated with urea efflux. However, in this study there was a positive correlation between changes in blood volume and the extracellular sodium concentration.…”
Section: Discussionsupporting
confidence: 83%
“…This could explain why these previous studies failed to observe significant differences. Fleming et al [14] studied blood volume changes during diffusive dialysis, and found no significant change in blood volume. However, in this study only 12 sessions with standard sodium concentrations were studied, and only 1 or 2 (17 in total) blood volume measurements were done, while in our experiment RBV was measured continuously during 60 sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the effect of blood volume reduction as one of the contributing factors, it is extremely important to carefully observe the distribution of fluids and sodium [3, 4, 5, 6, 7, 8, 9]. The sodium dialysate concentration has often been increased so as to obtain intradialytic cardiovascular stability [10].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only two reports exist regarding BV changes during diffusive dialysis (dialysis without ultrafiltration). Fleming et al [3] studied the effect of dialysate composition on intercompartmental fluid shift changes during 1.5 or 2 h of HD without net ultrafiltration using high, normal and low sodium dialysate. They concluded that dialysate composition affects the movement of water into and out of the plasma and erythrocytes in a manner that can be explained by altered plasma concentrations of osmotically active substances.…”
Section: Introductionmentioning
confidence: 99%